Love lockdown: dating, sex, and marriage in America's prisons - Greenwood, Elizabeth (Gallery Books)
"What is it like to fall in love through the bars of a prison cell? Elizabeth Greenwood spent five years investigating relationships between incarcerated people and their spouses on the outside. She profiled couples whose love through incarceration runs the gamut in terms of sexual orientation, race, and circumstances of their incarceration. A sort of Modern Love: Prison Edition, LOVE LOCKDOWN shows the authentic faces of the husbands and wives supporting some of the 2.3 million people incarcerated in the United States. Greenwood's investigation not only questions our assumptions about relationships through incarceration, but she also opens up under-reported facets of prisons and shines new insights on relationships in general. Greenwood takes the reader inside spaces that many have only heard whispers of-conjugal visit trailers, prison weddings, and more. She sits across a visiting room table from a woman convicted of a double homicide. She sifts through letters and drawings from Richard Ramirez with a former serial killer groupie. She goes to unseen places, teases out the complexities of these relationships, and shines a light on how they reflect desire and delusion we may all experience in our romantic pairings"--